NAVIGATING CLIMATE CHALLENGES: STRATEGIC DIRECTIONS FOR A SUSTAINABLE FUTURE - Krzysztof Goniewicz; Amir Khorram-Manesh; Frederick Burkle (Health Problems of Civilization)
This paper delves into six critical pathways to effectively address the climate crisis: (1) reinventing food systems, (2) preparing for population shifts, (3) upholding human rights, (4) investing in clean energy, (5) educating for a climate-conscious society, and (6) securing financial and political support. It underscores the need to make food systems resource-efficient and biodiversity-conscious. It emphasizes preparing for and managing population shifts due to climate-induced migrations with a specific focus on public health capacity and surveillance. Upholding human rights, particularly in the face of climate change-related challenges, is discussed in depth, highlighting the importance of social safety nets and policy safeguards. The report advocates for substantial investment in clean energy, including solar and wind power, and underscores the crucial role of energy efficiency. The significance of climate education is explored, emphasizing its role in fostering a climate-conscious society. The necessity of coordinated financial backing and strong political will in implementing climate strategies is also discussed. The paper concludes by affirming that collective will, global solidarity, and urgent actions are indispensable in combating climate change, advocating for a holistic approach that integrates these varied pathways.